Impact of ultrafast transport on the high-energy states of a photoexcited topological insulator - Freyse, F. (2019)
Ultrafast dynamics in three-dimensional topological insulators (TIs) opens new routes for increasing the speed of information transport up to frequencies a thousand times faster than in modern electronics. However, to date, disentangling the exact contributions from bulk and surface transport to the subpicosecond dynamics of these materials remains a difficult challenge. Here, using time- and angle-resolved photoemission, we demonstrate that driving a TI from the bulk-conducting into the bulk-insulating transport regime allows us to selectively switch on and off the emergent channels of ultrafast transport between the surface and the bulk. We thus establish that ultrafast transport is one of the main driving mechanisms responsible for the decay of excited electrons in prototypical TIs following laser excitation. We further show how ultrafast transport strongly affects the thermalization and scattering dynamics of the excited states up to high energies above the Fermi level. In particular, we observe how inhibiting the transport channels leads to a thermalization bottleneck that substantially slows down electron-hole recombination via electron-electron scatterings. Our results pave the way for exploiting ultrafast transport to control thermalization timescales in TI-based optoelectronic applications, and expand the capabilities of TIs as intrinsic solar cells.